Surgical Repair of Ectopia Cordis in a Sub-Saharan African Country (Benin) - Bori Bata, Abdel Kémal; Nékoua, Désiré; Ibrahim, Ahmad; Gogan, Boris; Zoumenou, Eugène (The Thoracic and Cardiovascular Surgeon Reports, 2025)
Ectopia cordis (EC) is an exceptionally rare congenital anomaly with a poor prognosis, particularly in resource-limited settings.We present a newborn with complete thoracic EC who underwent surgical correction on day 5 of life. Although cardiac repositioning and soft tissue coverage were achieved, the infant died 72 hours postoperatively from septic shock, reflecting the significant challenges faced in such contexts.This case underscores the urgent need for improved antenatal care and technical resources to enhance outcomes for complex congenital anomalies in sub-Saharan Africa.
Keywords: ectopia cordis; sternal agenesis; surgical correction; sub-Saharan Africa